PROBLEM OF DIAGNOSIS OF EARLY CONGENITAL SYPHILIS - G. P. Martynova; N. F. Kuznetsova (LLC "Diagnostics and Vaccines", 2015)
The paper presents a case of delayed diagnosis of early congenital syphilis in a child whose mother was observed in prenatal clinic starting from the 14th week of pregnancy. The child had specific skin rash already in maternity. The child was discharged home without examination in the hospital. Only manifestations of nephritis lead to admission of the child into an inpatient hospital. Only at the age of 1 month and 23 days the child was suspected of early congenital syphilis with severe polisimptomnym, and the patient was transferred to specialized hospital.